Determinants of Average Years of Schooling in Garut Regency: An Exploratory Factor Analysis Approach - Fitria, Dhina Amalia; Akbar, Gugun Geusan; Ulumudin, Aceng; Kania, Ikeu; Yudiardi, Dodi (Jurnal Edusci, 2025)
Background. Average School Length (RLS) is an important indicator in measuring the level of educational participation in a region. Garut Regency still faces challenges in improving RLS, which is influenced by various economic, social, and educational policy factors. Aims. This study aims to identify the main factors that affect RLS and analyze the differences in RLS between regions in Garut Regency. Methods. This study uses a quantitative approach with the Exploratory Factor Analysis (EFA) method to group interrelated variables into main factors. In addition, the ANOVA test was carried out to identify RLS differences between regions, with further tests by Bonferroni and Games-Howell to see the groups of regions that had significant differences. Result. The results of the analysis show that there are three main factors that affect RLS, namely (1) Economics and Accessibility of Education, (2) Educational Environment and Policy, and (3) Social Dynamics and Learning Motivation. Economic factors and accessibility have a dominant role, especially related to family income, education costs, and the availability of school facilities and transportation. The results of the ANOVA test showed a significant difference in RLS between regions (p = 0.011), with the Cisurupan area having a higher RLS than Limbangan and Pakenjeng. Conclussion. The findings of this study confirm that improving educational infrastructure, region-based policies, and the role of families and communities are very important in increasing school participation rates. Implication. The implications of this study encourage the need for more adaptive policy interventions to the socio-economic characteristics of the region and the strengthening of student motivation programs. Keywords: Average School Duration, Exploratory Factor Analysis, ANOVA, Educational Accessibility, Education Policy.